الأخلاق المهنية ودورها في تحقيق الأداء الوظيفي للعاملين - حوامدي,اكرام; دبش,عبد الرحمان (University of Eloued جامعة الوادي, 2024)
The study aims to know the role of professional ethics in the job performance of employees. To achieve the goal of the study, we followed the descriptive analysis method and chose a questionnaire tool to collect information. We chose a sample of 35 workers from a professor, an administrator, and a professional worker in the Faculty of Social and Human Sciences, El Oued University. The study concluded the following: - There is a correlation between respect and job performance - Commitment and mastery play a role in achieving employees’ job performance. - Respect plays a role in achieving employees’ job performance. - Honesty has a role in achieving employees’ job performance. تهدف الدراسة لمعرفة دور الأخلاق المهنية في الأداء الوظيفي للعاملين ولتحقيق هدف الدراسة اتبعنا المنهج الوصفي التحليلي واخترنا أداة الاستبيان لجمع المعلومات واخترنا عينة قدرها 35 عامل من أستاذ وإداري وعامل مهني في كلية العلوم الاجتماعية و الإنسانية جامعة الوادي وتوصلت الدراسة إلى التالي : - يوجد علاقة ارتباطية بين الاحترام والأداء الوظيفي - يوجد علاقة ارتباطية بين الالتزام والاتقان و الأداء الوظيفي للعاملين. - يوجد علاقة ارتباطية بين الصدق و الأداء الوظيفي للعاملين.
Keywords: الأداء الوظيفيذ; الأخلاق; المهنة; ethics; profession; job performance; commitment; mastery; respect; honesty